Public Employment and the Welfare State in Sweden - Rosen, Sherwin (Journal of Economic Literature, 1996)
This is a nontechnical summary of a much longer study which will appear with the same title in Richard Freeman, Birgitta Swedenborg, and Robert Topel, eds. (forthcoming). I am especially indebted to Henry Ohlsson and Birgitta Swedenborg, and to Stan Engerman, Vic Fuchs, Assar Lindbeck, Stephen Lundgren, and Agnar Sandmo for comments on initial drafts. I alone am responsible for the views expressed here.